Efficacy of timolol in the treatment of facial hemangioma and its effect on the proliferation and apoptosis of hemangioma stem cells: Treatment and impact of timolol on hemangioma - Zhu, Hongjian; Luo, Hua; Lai, Wenjuan (Cellular and Molecular Biology, 2023)
To investigate the efficacy of timolol in the treatment of facial hemangioma and the effect on the proliferation and apoptosis of hemangioma stem cells, 60 cases of children with IHs admitted to our hospital between 2020 and 2021 were selected and divided into two groups. The grouping was according to the lottery method, with 30 cases in each group. In the observation group, 0.5% timolol maleate eye drops were applied topically, and in the control group, propranolol hydrochloride tablets were administered orally to observe the efficacy of hemangioma, changes in hemangioma stem cells and the incidence of adverse reactions in both groups. Results showed that combined with the four-level score and ultrasound results, the number of effective treatment cases in the observation group was 28, which was higher than that in the control group, (P<0.05). The total number of adverse reactions in the observation group was 2, with an incidence rate. Under the intervention conditions of timolol, the proliferation level of hemangioma stem cells was inhibited, and the apoptosis rate of hemangioma stem cells increased with the increase of culture time (P<0.05). Among them, the apoptosis rate of the timolol group was higher than that of the blank control group at the same time point (P<0.05), and the difference was most significant at 48h (P<0.001). In conclusion, Timolol can effectively treat facial hemangioma in children, inhibit the proliferation of hemangioma stem cells and promote their apoptosis, with good curative effect, short treatment time and no obvious adverse reactions and it is economical and easy to accept.